Importância da mastofauna como ferramenta para conservação: estudo de caso do remanescente de Cerrado na UFSCar – campus São Carlos, SP - Silva, Melissa Freitas da (2023)
Recently, discussions about the future of environmental conservation have received greater attention. Still, it is shocking to observe that, even though the increase of information currently available, biodiversity continues to suffer frequent anxieties. The Cerrado is considered one of the most impacted domains due to habitat loss and fragmentation, and the concern with the effects of human disturbances on biological communities is even more urgent for medium and large mammals, which need larger areas for their survival. Observing the movement and behavior of species in situ and comparing these data to the history of land use in the region, we can provide a consistent basis for planning future management actions that aim at the effective conservation of native vegetation remnants. The objective of this work was to inventory mammalian fauna found in the Cerrado remnant located at the UFSCar, Campus São Carlos, to discuss the use of this taxonomic group as a tool for conservation of this area, and to carry out scientific dissemination of the results here found. The use of camera traps and linear transects were chosen as the main survey methodology, in addition to the comparison with previous data available from literature for the studied and adjacent regions. Nine camera traps were evenly distributed in three phytophysiognomies: three in the “cerrado sensu stricto”, three in the “mata de galeria”, and three at an Eucalipto plantation. In this study, 30 species of medium and large mammals were recorded, including species poorly known or at some threaten category such as: Myrmecophaga tridactyla, Sylvilagus minensis Chrysocyon brachyurus, Herpailurus yagouaroundi, Leopardus pardalis, Puma concolor, Mazama rufa and Dicotyles tajacu. M. tridactyla, Cabassous sp., Dasypus septemcinctus, P. concolor and L. pardalis, are new records for the area. Domestic animals and exotic invaders were also recorded, like “java-porcos”, highlighting the need to preserve the native species. The great diversity of mammals sampled in this work is the proof of the resilience of the Cerrado, in the sense that it can maintain viable populations of native species in the region, and serves as support for future projects to obtain higher legislative protection for this area and other native Cerrado vegetation remnants. A guidebook was developed for scientific dissemination of the data here obtained, and is available for public use.